Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas 2 SDN 10 Palu melalui Pendekatan Teaching at The Right Level (TaRL) dengan menggunakan Media Konkret - Santiasi, Ilo; Nurjannah; Pakiding, Mida (Cipta Media Harmoni, 2025)
There is an indication of low student learning outcomes; therefore, innovation in mathematics learning is needed to improve the quality and meaning of the learning process. The purpose of this study is to improve the mathematics learning outcomes of 2nd-grade students at SDN 10 Palu by implementing the TaRL (Teaching at The Right Level) approach, combined with the use of concrete media. The method used in this research is classroom action research, following the Kemmis and McTaggart model. The study was conducted in two cycles, each consisting of four stages: planning, action implementation, observation, and reflection. The collected data includes students' learning outcomes obtained through tests and observational data on teacher and student activities during the learning process. The results show that in Cycle I, the classical mastery level achieved was 68.96% (low category). However, in Cycle II, the success indicators were met, with the classical mastery level reaching 86.20% (good category). Therefore, learning in Cycle II has met the minimum success indicators in classical learning mastery. These findings indicate that implementing the TaRL (Teaching at The Right Level) approach, combined with concrete media, can significantly improve students' mathematics learning outcomes.